METABOLIC AND CARDIOVASCULAR RISK FACTORS IN YOUNG ADULTS WITH TYPE 2 DIABETES: THE ROLE OF LIPID ABNORMALITIES AND FAMILY HISTORY - SHETH NEHA DHARMESH; IVVALA ANAND SHAKER (Asian Journal of Pharmaceutical and Clinical Research, 2025)
Objective: Cardiovascular diseases (CVDs) are a major cause of illness and death worldwide, with dyslipidemia and insulin resistance contributing significantly to their development. Although these metabolic conditions were once considered prevalent mainly in older adults, these conditions are increasingly seen in younger populations due to lifestyle changes, obesity, and genetics. Early identification of high-risk individuals is crucial, yet research on these conditions in young adults is limited. Objective: This study aimed to investigate the relationship between lipid profiles, insulin resistance, and cardiovascular risk factors in young adults, especially those with a family history of diabetes. Methods: A cross-sectional case–control study involved 200 participants (aged 25–35 years), including 70 diabetic patients with a family history, 70 without, and 60 healthy controls. Cardiovascular and metabolic parameters, including waist circumference, body mass index, blood pressure, triglycerides (TG), high-density lipoprotein (HDL), total cholesterol, fasting blood sugar (FBS), hemoglobin A1c (HbA1c), and TG/HDL ratio, were measured. Insulin resistance was assessed using the homeostatic model assessment of insulin resistance (HOMA-IR). Results: Significant differences in metabolic and cardiovascular parameters were observed between diabetic patients and controls, especially in those with a family history. Diabetic patients with a family history had systolic blood pressure (131.5±12.90 vs. 121±16.9), TG (183.4±114.9 vs. 114±54.3), FBS (128.9±31.14 vs. 97.4±21.6), HbA1c (6.06±0.8 vs. 5.39±0.44), and TG/HDL ratio (4.22±2.42 vs. 1.04±0.28). A positive correlation was found between HOMA-IR and FBS, HbA1c, insulin levels, and TG, indicating a strong link between insulin resistance and these metabolic disturbances. Conclusion: The findings highlight the importance of early metabolic health assessments and interventions, particularly for young adults with a family history of diabetes, to reduce CVD risk. Further research is needed to explore the long-term cardiovascular impacts of early metabolic dysfunction.